Fourier-Transform Infrared Absorption Spectroscopy in Binary Hydrocarbon-Alcohol Single Droplet Evaporation. (17th February 2016) - Daly, Shane R.; Olson, Nicholas; Hagen, Christopher L.
Abstract : Broadband absorption spectroscopy, by way of FTIR, was used to investigate the vapor cloud of a single millimeter sized liquid droplet suspended by a syringe as it evaporates at standard conditions. Single beam data were collected every 8 seconds resulting in a time-resolved record. Species concentrations were tracked using their resonant absorption peaks and correlated with a multidimensional numerical model. The numerical model combined a Gaussian beam transmission through a temporally changing spherical vapor cloud with radial concentration gradients, informed by the D 2 law and interpreted using the Abel transform. There was fair agreement with temporal evaporation trends for single component runs. Multicomponent experiments of ethanol and isooctane showed synergistic blending effects and preferential evaporation of ethanol. Droplets were also suspended by a thermocouple to track the droplet temperature over time as they were subject to evaporative cooling. This work is the foundation of a basic technique for collecting useful data to inform a complex transport problem.